Propuesta de mejora a través del enfoque a procesos, para el laboratorio de hormigón de la FIIC ULVR - Chumbi Lema, Gilda Juliana (2024)
The present topic focuses on "Improvement proposal through the process approach, for the Concrete Laboratory of the FIIC (ULVR)", therefore its purpose is to standardize the processes in the practices and tests to be carried out in the laboratory, aimed at the students and staff who use it, focusing them on the correct use of the equipment and tools whose purpose is to guarantee that every time a test or practice is carried out, it is done in the same way regardless of who does it or when. be carried out. Therefore, the composition of a process scheme is very important to improve the practical tests that students can carry out in the concrete laboratory, allowing them to strengthen their knowledge and abilities. The methodology is integrated by a descriptive scope which seeks to specify important properties and characteristics of any phenomenon that is analyzed, on the other hand, the exploratory scope, details the operating procedures and management skills of the laboratory, including workflows, tools, roles. of teachers and students, and formal and informal procedures, with the aim of understanding the current situation and identifying areas for improvement...